To Segment or Not to Segment Markets? A Note on the Profitability of Market Segmentation for an International Oligopoly - Fredrik Gallo (Lund University, School of Economics and Management, Department of Economics, 2010)
Recent research on endogenous market segmentation finds that a monopoly's expected profit under perfectly segmented markets increases (relative to its profits under perfectly integrated markets) with exchange rate volatility. The firm thus has an incentive to make consumer resale increasingly difficult. We show that such an incentive may be absent for two firms competing in a Cournot fashion. While limitless consumer arbitrage forces a monopolist to deviate from its optimal pricing policies, it acts as a "disciplining device" helping the Cournot duopoly to approach and commit to the cartel solution in some markets. The firms' total profit may hence be higher when they engage in integrated-market pricing and neither firm would have an incentive to take on additional costs to facilitate segmenting.
Keywords: D43; F31; L13; 330; arbitrage; Cournot duopoly; exchange rate volatility; market segmentation; third degree price discrimination